2020
DOI: 10.1039/c9ra10527a
|View full text |Cite
|
Sign up to set email alerts
|

Study of the discharge/charge process of lithium–sulfur batteries by electrochemical impedance spectroscopy

Abstract: Schematic model for the electrochemical reaction mechanism of a sulfur electrode in the discharge process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 35 publications
4
55
0
Order By: Relevance
“…The Nyquist plots of all the cells consisted of a semicircle in the high‐ and medium‐frequency regime and an inclined line in the low‐frequency regime. The EIS analyses indicate that the charge‐transfer resistance ( R ct ), [ 20 ] represented by the semi‐circle, decreases as the amount of LiNO 3 increases, to 77.5, 56.5, and 50.3 Ω for the DMI‐LNO‐0 m , 0.2 m , and 0.5 m cells, respectively, once again pointing to the stabilization of the Li metal interface by the addition of LiNO 3 .…”
Section: Figurementioning
confidence: 99%
“…The Nyquist plots of all the cells consisted of a semicircle in the high‐ and medium‐frequency regime and an inclined line in the low‐frequency regime. The EIS analyses indicate that the charge‐transfer resistance ( R ct ), [ 20 ] represented by the semi‐circle, decreases as the amount of LiNO 3 increases, to 77.5, 56.5, and 50.3 Ω for the DMI‐LNO‐0 m , 0.2 m , and 0.5 m cells, respectively, once again pointing to the stabilization of the Li metal interface by the addition of LiNO 3 .…”
Section: Figurementioning
confidence: 99%
“…Here, we postulate that the solvation effect and intermediate chemical dissolution of the catholyte could significantly deviate from the practical limits [20,33] . To this end, we implement electrochemical impedance spectroscopy (EIS), a non‐invasive technique capable of monitoring the state of charge/discharge and state of health of the battery [52,53] . In the NaS system, the chemical composition of the catholyte follows a sequential reversible change on electrochemical charge/discharge [8,53] .…”
Section: Resultsmentioning
confidence: 99%
“…[20,33] To this end, we implement electrochemical impedance spectroscopy (EIS), a non-invasive technique capable of monitoring the state of charge/discharge and state of health of the battery. [52,53] In the NaS system, the chemical composition of the catholyte follows a sequential reversible change on electrochemical charge/discharge. [8,53] The EIS data revealed that the catholyte contributes heavily to the ohmic resistance ( Figure S2 & equation S1).…”
Section: Approach To Implement the Revised Charge-discharge Cut-off Lmentioning
confidence: 99%
See 2 more Smart Citations